Assessment of protein–protein interfaces in cryo-EM derived assemblies - Sony Malhotra (Nature Portfolio, 2021)
Here, the authors present Protein Interface-score (PI-score), a machine learning-based metric that has been trained on protein–protein interfaces’ features from high-resolution crystal structures. They use the PI-score to evaluate the protein–protein interfaces in more than 1000 PDB-deposited cryo-EM structures and show that it can be used as a complementary assessment tool for cryo-EM model validation.